FEATURES OF THE ENGLISH PRESS. - Khasanova Kamila Bakhtiyorovna; Safarova Dilorom Abdukadirovna (Scholar Express Journal, 2023)
This article tells about some features of British and American newspapers. Today, the press occupies a special place in human life. The article gives different opinions of linguists about the features and general characteristics of British and American newspapers. Factors such as technological progress and general education actively interact with each other
Keywords: newspapers; linguistics; information; technology